(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Typhoid fever has become a significant health problem causing an estimated 21.7 million cases per year and over 200,000 deaths annually. This study analysed typhoid fever mortality spatially and temporally in Kano State over the period of 10 years (2006-2015). Hospital records obtained from all General hospital (31) and Aminu Kano Teaching Hospital were used. These facilities were purposively selected because of the availability of doctors and diagnostic laboratories. Coordinate of wards in the state were also generated and imported into Arc GIS environment. Variables used include age, sex, number of days spent on admission, condition on discharge and Typhoid fever mortality cases. Descriptive statistics (Tables) was used to show age and sex distribution of deaths while bar graphs were used to show case fatality. The results showed case fatality rate for the state is at 6% with Kunchi in the extreme north east having the highest case fatality rate greater than 10% and the lowest rates of 0-3% were observed around Doguwa Tudun Wada and Takai. Furthermore, results revealed that more females died of the disease than males with 6.3% and 5.6% respectively, while the monthly distribution of mortality in the state for all the years showed that it was high in months of March and December with over 6% and about 7% case fatality respectively. The study recommends frequent vaccination and hygienic eating and drinking habits as well as hygienic practices at home and outside home as remedies for addressing the problem.